Molecular identification and antimicrobial activities of Bacillus subtilis MS-01 isolated from Indonesian ethnic food lemea - MARDHATILLAH SARIYANTI; PEGI MELANTI ADRI; RISKY HADI WIBOWO; AHMAD AZMI NASUTION; THORIQUL HIDAYAH; SIPRIYADI SIPRIYADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sariyanti M, Adri PM, Wibowo RH, Nasution AA, Hidayah T, Sipriyadi. 2025. Molecular identification and antimicrobial activities of Bacillus subtilis MS-01 isolated from Indonesian ethnic food lemea. Biodiversitas 26: 1069-1074. The community in Bengkulu Province has a variety of traditional foods produced through fermentation, one of which is a bamboo shoot-based dish known locally as lemea. Bacillus subtilis, found in fermented foods, shows great potential as a probiotic due to its ability to inhibit harmful bacteria. Given its genetic diversity, molecular identification is crucial to differentiate between strains. This study represents the first isolation and identification of Bacillus strains from lemea, an ethnically fermented bamboo shoot from the Rejang tribe community in Bengkulu, Indonesia. This study aimed to evaluate the antibacterial activity and perform molecular identification analysis using the 16S ribosomal RNA gene region. The Bacillus isolate was identified using observations of macroscopic and microscopic morphological Lactic Acid Bacteria (LAB). Inhibition tests of Bacillus isolate were conducted using pathogenic bacteria, namely Escherichia coli, Salmonella typhimurium, and Enterococcus faecalis. The isolate demonstrated an exceptionally strong inhibitory effect, particularly against E. faecalis. Molecular identification involved polymerase chain reaction amplifying the 16S rRNA gene, producing an amplicon of approximately 1,300 base pairs. Sequence analysis via BLAST showed 99.84% similarity to B. subtilis strain X2, SSR17, NIBSM OsG1, BaBc-1, and strain LMV in GenBank. Phylogenetic analysis confirmed the isolate’s classification within the order Bacillales and family Bacillaceae. In conclusion, B. subtilis MS-01 was successfully isolated and identified, exhibiting antibacterial potential against both Gram-negative and Gram-positive pathogenic bacteria, with a particularly noteworthy effect against E. faecalis, thereby suggesting its potential as a probiotic with potent antimicrobial properties.